ANALISIS PENGARUH JUMLAH PENDUDUK, INFLASI, DAN NILAI TUKAR TERHADAP PERTUMBUHAN EKONOMI PENDEKATAN VECM - Puji Astuti, Chanifah; Prasetyanto, Panji Kusuma (Transpublika Publisher, 2022)
Economic growth is a goal that every country wants to achieve. Economic growth in Indonesia is influenced by many factors. This study aims to analyze the effect of the exchange rate, population and inflation on economic growth in Indonesia for the period 1990-2019. The method used in this research is the Vector Error Correction Model (VECM) after it is known that there is cointegration in the VAR model testing. From the research results, it is stated that the Consumer Price Index (CPI) variable has a relationship with Economic Growth in the long term. Then in the short-term relationship, the population variable with the highest R-square value is 0.981823. Meawhile, the results of Variance Decomposition show the effects that occur due to shocks from changes in one variable to other variables occur in various ways.